Techno‐economic comparison of amine regeneration process with heat‐stable amine salt reclaiming units. Issue 12 (21st October 2021) - Lim, Jonghun; Lee, Jesung; Moon, Il; Cho, Hyungtae; Kim, Junghwan
Abstract: Most factories employ an amine gas sweetening process to remove sulfur compounds. During this process, heat‐stable amine salt (HSAS) is generated, which reduces process efficiency. Ion exchange resin and electrodialysis reclamation methods are employed for HSAS removal. However, the equipment cost, electricity, water, and raw material consumption of each unit vary according to the amount of HSAS reclaimed; thus, it is necessary to consider the cost. In this study, we compared the techno‐economic aspects of the amine regeneration process for individual HSAS reclaiming units, developed process models to predict operation costs, and verified our simulation results by comparing actual operation and design data. The proposed mathematical models can be employed to calculate various costs incurred during amine regeneration with HSAS reclaiming units. The economic crossover point is derived at 36.6111 kg‐mol/d by utilizing the models. This enables economically feasible units to be identified based on the amount of HSAS reclaimed. Abstract : First, considering each HSAS reclaiming unit, the developed process models can be used to predict costs such as equipment, raw materials, electricity, and water costs under various conditions. Second, the proposed mathematical model can be used to calculate all types of costs incurred by the amine regeneration process with the HSAS reclaiming unit, which depends on the amount of HSAS reclaimed per day. Finally, the economic crossover point derived using the developed models will lead to significant economic improvement when installing an HSAS reclaiming unit in many processes, as shown by our quantitative comparison of the cost according to reclaimed HSAS amount.